Horizontal light pipe transporter for deep plan high-rise office daylighting in tropical climate - Heng, C. Y. S. (Elsevier Ltd, 2020)
Despite having abundance of daylight in tropical climate, many high-rise offices do not exhibit good daylight condition. Economic profits have led to the blooming of deep open-plan design which causes non-uniform daylight distribution especially in the deep area. Light pipe (LP) provides a solution to transport daylight into the interior. Daylighting performance of nine LP transporter shapes with different numbers of side and extractor openings were analysed using computer simulation software, Integrated Environment Solution Virtual Environment (IESVE) and validated with a physical scale-model experiment. Validation results showed significant Pearson correlations that ranged from 0.9170 to 0.9544. Simulations were carried out under overcast sky and intermediate sky with sun conditions. The results showed that all of the LP cases improved the daylighting performance of an empty open-plan office room. The semicircle transporter with two openings, which has 14% less surface area than a typical rectangular transporter, showed the best performance both quantitatively and qualitatively. This helps to save cost in terms of material usage and creates additional spaces for wiring and ducting in the plenum. This study also concluded that the shape of the LP transporter affects the efficiency of LP while the influence of the number of polygon sides and height of the sides, without altering the overall height of the transporter, are not significant. Thus, the findings of this study promote the usage of LP in deep open-plan high-rise office buildings by proposing design recommendations and guides for building designers.